Práticas de letramento de professores de matemática em formação na licenciatura em educação do campo - Fernandes, Fernando Luís Pereira (Universidade Federal de São Carlos, 2019)
This research has as its goal the comprehension of the literacy practices engaged and problematized by Rural Education undergraduates. To answer the guiding question: Which literacy practices of the future teacher can be highlighter in a Rural Education Undergraduate Course?, we based ourselves in references for Rural Education, Literacy and Numeracy Studies and Teachers’ Education for Social Justice. The methodology of the research is of qualitative nature, and the structuring of the data happened in two steps. The first of them in a discipline about Functions, taught by the researcher, who is also a professor in the Rural Education Undergraduate Course (LECampo) of the Federal University of Triângulo Mineiro and had the participation of 45 undergraduates, as subjects of the investigation. In this step, the tools used were: questionnaire of socio-economical nature, applied to all the undergraduates, and video recordings of the classes. The second step of the data production happened with the involvement of twelve of the undergraduates, subjects of the survey, who chose Mathematics, with the data being obtained through semi structured interviews. Thus, it was constituted as material to be analyzed in investigation: questionnaire results, students’ written productions, transcription of parts of the classes and interviews. After the data organization, we constructed two analysis axes: (i) Technical Tendency of Mathematics Teaching and its Variations as Representation of Autonomous Literacy Model and (ii) Formative actions at LECampo as driving forces behind literacy practices of future teachers. The data showed us that, despite the basic schooling of the undergraduates being based on a technical and procedural dimension, and thus, having produced literacy practices common to the autonomous model, different formative actions in LECampo’s degree made it possible for the teachers the mobilization and problematization of literacy practices,– the formulation of problems and financial of familiar farming. In particular, the undergraduates in Mathematics have exposed during the interviews their ways of seeing and conceiving the teaching of Mathematics, with emphasis for the Empirical-Activist and Socioethnocultural teaching tendencies. The identified characteristics of those tendencies can contribute to the comprehension of literacy events and practices valued by the undergraduates. The results point at the many literacy practices highlighted in the Rural Education Initial Teacher Education and for the necessity of depth and continuity of those studies.

Esta investigación tiene como objetivo general comprender las prácticas de literacidad movilizadas y problematizadas en la formación inicial de maestros en Educación Rural. Para responder a la pregunta orientadora: ¿Qué prácticas de literacidad del futuro maestro pueden ser destacadas en un curso de Licenciatura en Educación Rural?, nos apoyamos en referenciales de la Educación Rural, de los Estudios de Literacidad, Numeracia y de la Formación de Maestros para la Justicia Social. La metodología de la investigación es de naturaleza cualitativa y la construcción de los datos ocurrió en dos etapas. La primera de ellas en una asignatura sobre Funciones, ministrada por el investigador, también profesor en el curso de Licenciatura en Educación Rural (LECampo) de la Universidad Federal del Triângulo Mineiro y contó con la participación de 45 futuros maestros como sujetos de la investigación. En esta etapa, los instrumentos utilizados fueron: cuestionario de naturaleza socioeconómica, aplicado a todos los futuros maestros, y la grabación en video de las clases. La segunda etapa de la producción de los datos se dio con la participación de doce de los estudiantes, sujetos de la investigación, que escogieron la Habilitación en Matemáticas, siendo los datos obtenidos mediante entrevistas semiestructuradas. De este modo, se constituyó como material a ser analizado en la investigación: resultados del cuestionario, producciones escritas de los estudiantes, transcripción de extractos de las clases y de las entrevistas. Después de la organización de los datos, construimos dos ejes de análisis: (i) Tendencia Tecnicista de Enseñanza de Matemáticas y sus Variaciones como Representación del Modelo Autónomo de Literacidad y (ii) Acciones formativas en LECampo como movilizadoras de prácticas de literacidad de futuros maestros. Los datos revelaron que, a pesar de que la escolarización básica de los estudiantes se basaba en una dimensión tecnicista y procedimental y, por lo tanto, haber producido prácticas de literacidad típicas del modelo autónomo, diferentes acciones formativas en el curso de la LECampo posibilitaron a los futuros maestros la movilización y la problematización de prácticas de literacidad, - la formulación de problemas y la organización financiera de la producción agrícola familiar. En particular, los futuros maestros de Matemáticas expusieron en las entrevistas sus modos de ver y concebir la enseñanza de Matemáticas, con destaque para las tendencias de enseñanza Empírico-Activista y Socioetnocultural. Las características identificadas de estas tendencias pueden contribuir en la comprensión de eventos y prácticas de literacidad valorados por los licenciandos. Los resultados apuntan a las varias prácticas de literacidad resaltadas en la formación inicial de maestros en Educación Rural y para la necesidad de profundización y continuidad de esos estudios.
Literacy practices of pre-service mathematics teachers in rural education undergraduate course
Prácticas de literacidad de futuros maestros de matemáticas en un curso de educación rural
Keywords: Educação do campo; Letramento docente; Formação Inicial de Professores de Matemática; Formação de Professores para a Justiça Social; Ensino culturalmente relevante; Rural education; Teacher literacy; Mathematics Teacher Initial Education; Social Justice Teacher Education; Culturally relevant pedagogy; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO